A Literature Review on the Continuing Professional Development (CPD) for Accounting Teachers: Perspective of Government Colleges in Bangladesh (Global Journal of Management and Business Research, 2022)
Teachers' Continuing Professional Development (CPD) is a highly discussed issue nowadays worldwide due to its significant role in upholding the professional skills of the faculties. Continuing professional development (CPD) is easy to recognize but relatively difficult to define. Because of its formal and informal practices, the scope and concept of the CPD surround theoretical and empirical controversy. Dissimilar concepts of formal training and in-service learning make the issue more confusing. However, Day's (1999) definition of CPD covers each behavior that aims to bring changes in the classrooms. In Bangladesh, teachers' continuing professional development (CPD) is yet to get appropriate attention from teachers, institutional authorities, and education policy planners.
Keywords: CPD; teaching; accounting; bangladesh